The Capital Complex : Beijing’s New Creative Clusters - Keane, Michael (Springer, 2009)
This essay begins with a brief discussion of how the idea of creative industries has provided the impetus for a new phase of cultural infrastructure construction in Beijing. I then contextualise these developments with an abridged history of the city from the time it became the imperial capital in 1420. A walled city of four separate enclosures during Yuan, Ming and Qing dynasties, by the 1950s Beijing had transformed into a sprawling city of industrial districts. The economic reform period which began in 1979 saw a transition from Maoist revolutionary class struggle to a pragmatic model of economic reconstruction and modernisation under Deng Xiaoping. An ensuing boom in development led to a surge in urban migration, putting further pressure on infrastructure. During the mid-1980s several of China’s large cities, notably Shanghai, Shenzhen, Guangzhou, Tianjin and Beijing began to compete with each other, attempting to lure international investment. Beijing assumed a capital complex; not only was it the centre of political power, it saw itself as the cultural centre of the new China.